The Effectiveness of Game Based Learning Utilizing Snakes and Ladders Media on Javanese Script Learning Outcomes - Fitriani, Citra Dwi; Insani, Nur Hanifah (Universitas Pendidikan Ganesha, 2024)
This research is motivated by students' difficulties in writing Javanese script. The purpose of this research is to determine the effectiveness of using a game-based learning model using a snakes and ladders media on students' learning outcomes in writing Javanese script in fifth grade. The type of research used is quantitative research with an experimental method. The research design uses a quasi-experimental design with the type of research being one group pretest-posttest design. The population and sample in this research were fifth grade students totaling 27 students. The sampling technique in this research uses purposive sampling technique, where samples are taken with certain criteria. Data collection methods in this research were observation, tests, and documentation. Based on the research results, a paired sample t- test was obtained at 0.000 and an N-Gain test at 0.5321. The results of the data analysis indicate that the game-based learning model mediated by snakes and ladders is effective enough to improve students' learning outcomes in writing Javanese script. Thus, it is expected that the game-based learning model using snakes and ladders media can have a positive impact on improving learning outcomes in writing Javanese script.